ANALISIS KETERSEDIAAN DAN KEBUTUHAN SUMBER AIR DI DESA SIDOMULYO - Indarto Indarto; Suhardjo Widodo; Ninin Ismulayati (JURNAL AGROTEKNOLOGI, 2011)
This article expose water demand and supply analysis for rural smallholders. The case study was done in Sidomulyo Village, Jember, East Java. Research metodhology include : (1) data inventory, (2) water demand, (3) water supply, (4) water balance analysis, and (5) Optimalisation using Linear Programming. Data was inventored by means of: land surveying, discharge measurement, water sampling, and questioner. Water supply was calculated by measuring discharge from the sources of water. Water demand was calculated by classifing user on three classes: (a) residential use, (b) poultry, and (c) coffee-processing-unit. Water balance was calculated by considering demand and suplly. Result showed that water supply form discharge is sufficient as compared to total water demand of the Sidomulyo village. Analysis using Linear Programming show the optimal water can be used for coffee processing unit during the two seasons.Keywords: Water Supply, Water demand, Water Balance, Linear Programing, Smallholder village